CLINICAL PRACTICE OF MANAGEMENT OF VARICELLA AT CHILDREN AT THE PRE-HOSPITAL STAGE IN NOVOSIBIRSK CITY - Елкина, Татьяна Николаевна; Пирожкова, Наталья Игоревна; Грибанова, Ольга Александровна; Лиханова, Маргарита Геннадьевна (Mother and Baby in Kuzbass, 2019)
The aim of the research – assess the clinical and epidemiological features of the varicella and analyze the treatment tactics of children with varicella in the polyclinics of the Novosibirsk city. Materials and methods. An analysis of 100 outpatient cards of children (age range from 8 months to 14 years) who had varicella and were on an outpatient treatment was carried out in 2013-2016. Results. The majority of patients are school- and day care children with a burdened epidemiological history, the average age of 4.9 years, who had varicella of light severity. The greatest number of cases was observed from April to July. The disease proceeded on a favorable premorbid background and had a benign course. The duration of the disease averaged 11 days. The intoxication syndrome manifested mainly with a fever lasting 3.1 days. The number of patients with abundant and uneventful rashes was identical. The duration of the exanthema syndrome was 4.7 days. Symptomatic treatment consisted of use of antihistamines and staining of the elements with aniline dyes and antipyretic drugs. Anaferon for children and acyclovir were most commonly used among the etiotropic therapy medicamentations. Conclusion. The Novosibirsk region is an area with high rates of varicella morbidity, higher than Russia’s average by 15-30 % over the past seven years. The structure of the affected by the disease is similar to the country average. The change in seasonality is registered, with the rise in the incidence rate in the spring-summer period. Diagnosis was carried out taking into account the basic diagnostic signs: an indication of contact with the varicella patient, the presence of symptoms of intoxication, fever and a typical exanthema. Most patients received only symptomatic treatment. Anaferon for children was most commonly used among the etiotropic therapy medicamentations. The unique mode of action of RAII (Release-Active Interferon Inducers) explains the wide possibilities for their application, especially for children with relatively mild chiken pox. The approval of the primary health care standard for children with moderate varicella would help to regulate the approach for the antiviral drugs selection and avoid polyprogram treatment.